Current and possible future impacts of the tree-killing polyphagous shot hole borer beetle in a Southern Afrotemperate forest complex in South Africa - Van Rooyen, Elmar (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScConsEcol)--Stellenbosch University, 2021.